Constructability comparison between IBS and conventional construction - Ehsan Harirchian, 1989- author; Abdul Kadir Marsono, supervisor; Fakulti Kejuruteraan Awam (2015)
Thesis (Sarjana (Kejuruteraan Awam - Pengurusan Projek)) - Universiti Teknologi Malaysia, 2015